HIBRIDITAS MULTIDIMENSIONAL: STUDI KASUS KARYA MUSIK KOMUNITAS BADAN GILA - Sudirga, Komang (Institut Seni Indonesia Denpasar, 2020)
This paper wants to show that the Komunitas Bada Gila (or Crazy Body Community) is an art community in Telepud Village, Tegalalang District, Gianyar Regency. This research is directed to answer questions related to the existence, aesthetic foundation, and creative processes that are behind the show. To answer these qualitative questions, this study applies various techniques and procedures for collecting data in the form of interviews and observations. I find that this community was founded in 2008 by 16 artists who have a commitment to devote their lives in the ecosystem of the art world. The idea to build this art community began with the Final Project of Artwork by Wayan Sutapa, which was inspired by genjek, the song that was played while drinking wine. Initially Sutapa aims to change the perception of traditional art which is considered as the 'art of the drunk' by placing it in a new context. However, instead of changing these negative perceptions, the works of the community have opened the possibility of expanding the creativity of kecak and genjek art into a more attractive form with the body as the medium. The creative works of the community reaffirm that Balinese society is open and a necessity for local-global struggle and association in Bali.